Living in and learning within urban space. Inviting teacher students to exchange their city life experiences with words and drawing - Samira Jamouchi (European Teacher Education Network, 2018)
Cities open themselves up to different ways of being explored, experienced, and expressed by the inhabitants. Newcomers and natives each bring unique perspectives on the cities they inhabit. This paper describes an arts-based research design I call "visual dialogue," in which I ask personsto express, through drawings and words, their subjective urban experiences. The ongoing drawing process itself, rather than any finished product, is the heart of this practice. In this paper, I give one examples of a Visual Dialogues and I present some philosophical perspectives that can motivate art and crafts teachers to engage with more fluid and explorative teaching practice in the subject of art and craft, connected to urban experience. Especially in international classes with university students as a means of fostering communication across cultural and individual differences.